Impact of entrepreneurial activity and ICT development on sustainable development: evidence from high-income countries - Karabetyan, Lina (MDPI, 2023)
Sustainable development has become a vital issue in the globalizing world given the food insecurity, climate change, significant degradation of the environment and depletion of natural resources, and biodiversity loss. Therefore, the identification of the key factors behind sustainable development is important for the planning and application of the proper policies by countries. In this context, the institutional, demographic, social, and economic determinants of overall sustainable development have been extensively explored, but the interplay among sustainable development, en trepreneurial activity, and ICT development has stayed relatively untouched. This article investigates the effect of entrepreneurial activity, proxied by total early-stage entrepreneurial activity and ICT development, on the overall sustainable development of 15 high-income countries over the 2002–2018 period; it uses the Westerlund and Edgerton cointegration test with a structural break, taking notice of the gap in the empirical literature regarding the determinants of sustainable development. The cointegration analysis shows that entrepreneurial activity and ICT development have a positive influence on sustainable development in the long run, but that the effect of ICT on overall sustainable development is shown to be stronger in comparison to entrepreneurial activity. ICT penetration and entrepreneurial activity should be encouraged through institutional, educational, and fiscal incentives to make progress in sustainable development.
Keywords: Entrepreneurial activity; ICT development; Sustainable development; Cointegration analysis